2018
DOI: 10.1002/bmc.4205
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurement of NAD metabolome in aged mice tissue using liquid chromatography tandem‐mass spectrometry

Abstract: Nicotinamide adenine dinucleotide (NAD) is a major co-factor that mediates multiple biological processes including redox reaction and gene expression. Recently, NAD metabolism has received considerable attention because administration of NAD precursors exhibited beneficial effects against aging-related metabolic disorders in animals. Although numerous studies have reported that NAD levels decline with aging in multiple animal tissues, the pathway and kinetics of NAD metabolism in aged organs are not completely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 28 publications
(39 reference statements)
0
29
0
Order By: Relevance
“…Although little is known about the relationship between declining NAD + levels and CKD, it is plausible that augmentation of NAD + may also have a therapeutic role in slowing CKD progression. More work is needed to develop methods that can interrogate NAD + , NADH, NADP + , NADPH, their respective precursors and their intermediates in kidney tissue to understand how NAD + metabolism is impacted by ageing, both in experimental organisms and in humans 99 .…”
Section: Age-related Loss Of Kidney Functionmentioning
confidence: 99%
“…Although little is known about the relationship between declining NAD + levels and CKD, it is plausible that augmentation of NAD + may also have a therapeutic role in slowing CKD progression. More work is needed to develop methods that can interrogate NAD + , NADH, NADP + , NADPH, their respective precursors and their intermediates in kidney tissue to understand how NAD + metabolism is impacted by ageing, both in experimental organisms and in humans 99 .…”
Section: Age-related Loss Of Kidney Functionmentioning
confidence: 99%
“…1 months old)Enzymatic[22]Male C57BL/6 N mice (24 months old v.s. 3 months old)LC/MS[19]Adipose tissueC57BL/6 mice (25–31 months old v.s. 3–6 months old)HPLC[8]Male C57BL/6 mice (32 months old v.s.…”
Section: Introductionmentioning
confidence: 99%
“…We also determined levels of the NAD precursor NAM in these mice and observed no changes due to HFD feeding in WT and Nmnat3 Tg mice (Supporting information Figure S1A). Because many studies have indicated that skeletal muscle NAD levels decline with aging (Frederick et al., 2016; Yaku, Okabe, & Nakagawa, 2018; Zhang et al., 2016), we determined NAD levels in WT and Nmnat3 Tg mice at the ages of 4, 18, and 24 months. Nmnat3 Tg mice had twofold higher NAD levels than WT mice at 3 months of age.…”
Section: Resultsmentioning
confidence: 99%
“…MS settings and chromatographic conditions were used as described previously (Yaku et al., 2018). TCA cycle intermediates were analyzed by selected ion monitoring (SIM) using Agilent 5977 MSD Single Quad mass spectrometer coupled to Agilent 7890 Gas Chromatography.…”
Section: Methodsmentioning
confidence: 99%